Causes and Consequences of Compulsive Buying Behavior: The Moderator Effects of Gender and Generation - Chalermjirapas, Darunee; Suwanragsa, Issara (Journal of Community Development Research (Humanities and Social Sciences); Vol 16 No 3 (2023): July - September 2023DO - 10.14456/jcdr-hs.2023.30, 2023)
Compulsive buying has received attention from academicians in several countries. Past empirical studies (i.e. of Achtziger et al., 2015; Donnelly et al., 2013; Gupta, 2013; Moon & Attiq, 2018) emphasized on some personality factors, (i.e. materialism, self-esteem, and self-control) that influence compulsive buying behavior. The present study fills this gap by: 1) incorporating delay-gratification as another important trait factor affecting compulsive buying behavior, 2) simultaneously examining the influence of personality traits on compulsive buying behavior and its effects on credit card usage and credit card debts, and 3) observing variations of study results among different groups of gender and generation (Gen X, Gen Y, & Baby Boomers). Data are collected from 550 shoppers who hold credit cards at the 11 shopping malls in Bangkok. Results from Structural Equation Model indicated that 1) materialism has a positive influence on compulsive buying behavior, while self-control, self-esteem, and delay-gratification have negative influences on compulsive buying behavior, 2) there is a positive influence of compulsive buying behavior on credit card usage and credit card debts, 3) in examining the moderating role of gender and generation on the relationships among the personality traits, compulsive buying behavior, and financial behaviors, the multigroup analysis has revealed that gender has a moderating effect on the relationship between self-control and compulsive buying behavior only while, 4) generation (Gen Y versus Baby Boomers) has moderating effects on the relationships of materialism and delay-gratification on compulsive buying behavior, and the relationships between compulsive buying behavior and credit card debts. Keywords:   Causes and Consequences, Compulsive Buying Behavior, Credit Card Debts, Credit Card Usage, Gender, Generation, Structural Equation Model (SEM)